THE ROLE OF DEMOCRACY IN SUPPORTING INFRASTRUCTURE DEVELOPMENT IN EAST JAVA - Alif Firdaus Zamzam; Mahmud Aprian Mabruri; Midkholus Surur; Donny July Prasetyo (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
Infrastructure is an important element to facilitate the community in developing the level of Productivity and economic development. such as in East Java itself is one of the provinces with a fairly large area, so that infrastructure development in East Java still faces various challenges, such as disparities in development between regions, budget constraints, and coordination between the central and regional governments. Many factors influence it, one of which is Democracy which is implemented because this is a vital thing in running a government system, especially in Indonesia. With this phenomenon, researchers are interested in seeing the Condition, Infrastructure Development and the extent of the role of Democracy, this study uses the Literature Study method with a Qualitative Approach. This shows the fact that democracy needs to continue to be improved because the role of democracy itself aims to involve the participation of the community who directly feel the facilities from the government. Political participation of the community, the quality of political leadership, and the application of democratic principles, such as transparency, accountability, and law enforcement, are factors that contribute to encouraging infrastructure development in this area.